2019
DOI: 10.1101/770420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hsa_circ_0001947 suppresses acute myeloid leukemia progression by sponging hsa-miR-329-5p and regulating CREBRF expression

Abstract: 13Acute myeloid leukemia (AML) is a heterogeneous group of diseases resulting 14 from clonal transformation of hematopoietic precursors through the acquisition of 15 chromosomal rearrangements and multiple gene mutations. Accumulating evidence 16 has indicated that aberrantly expressed circular RNAs (circRNAs) are involved in 17 cancer development and progression. However, their clinical values and biological 18 roles in AML remain unclear. In this study, we identified the aberrantly 19 down-regulated prof… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The above discovery compelled us to investigate the mechanisms underlying its silencing, which could aid in the development of effective Circ_0001187-activating agents. The biogenesis of circRNAs has been reported to be regulated both co and posttranscriptionally in cells (5,7). Both Circ_0001187 and DOPEY2 linear mRNA are derived from DOPEY2 pre-mRNA, and consistently, our results showed that DOPEY2 mRNA expression was positively correlated with Circ_0001187 expression (Figure 2J).…”
Section: Characteristics Of Circ_0001187 In Aml Cellssupporting
confidence: 70%
“…The above discovery compelled us to investigate the mechanisms underlying its silencing, which could aid in the development of effective Circ_0001187-activating agents. The biogenesis of circRNAs has been reported to be regulated both co and posttranscriptionally in cells (5,7). Both Circ_0001187 and DOPEY2 linear mRNA are derived from DOPEY2 pre-mRNA, and consistently, our results showed that DOPEY2 mRNA expression was positively correlated with Circ_0001187 expression (Figure 2J).…”
Section: Characteristics Of Circ_0001187 In Aml Cellssupporting
confidence: 70%
“…Wong et al asserted that CREBRF was relevant to the regulation of high-density lipoproteinsinduced angiogenesis [37]. And Han et al announced that CREBRF worked as an inhibitory role in AML progression [19]. In accordance with this finding, CREBRF knockdown could reverse the inhibition of NEAT1 on AML progression, implying CREBRF was a repressor of AML.…”
Section: Discussionmentioning
confidence: 90%
“…CREB3 regulatory factor (CREBRF), a highly conserved protein, was reportedly acted as an anti-cancer gene of glioblastoma via obstructing the hypoxia-induced autophagy [18]. And CREBRF was shown to restrain the AML progression regulated by circRNA_0001947/miR-329-5p [19]. Nevertheless, it is unexplored whether CRE-BRF is a target for miR-338-3p and can be regulated by NEAT1 in AML.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the correlation between cir-cRNA expression and cell proliferation in hematological malignancies. For instance, circ-0004136 [60] promoted AML cell proliferation by sponging miR-142, while circ-0001947 [61] up-regulated CREBRF to repress AML cell proliferation by inhibiting hsa-miR-329-5p. In addition, circPOLA2 [62] and circ-0121582 [63] were overexpressed in AML and promoted cell proliferation by targeting their miRNAs.…”
Section: Circrnas Regulate the Proliferation Apoptosis Cell Cycle Inv...mentioning
confidence: 99%